PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM MENUNJANG KEGIATAN BELAJAR DAN MENGAJAR DI SMP MUHAMMADIYAH PARAKAN PAMULANG, KOTA TANGERANG SELATAN, BANTEN - Anthoni, Lukman; Faisal, Rahman; Fahmi, Darul (Jurnal Abdi Masyarakat Multidisiplin, 2024)
This community service activity aims to improve the quality of education at SMP Muhammadiyah Parakan Pamulang through the utilization of Artificial Intelligence (AI). Using a school-needs-based approach, the program includes situational analysis, interactive training, and technical assistance for students and teachers. The lecture method was employed to introduce AI and its applications in education, while the discussion method encouraged active participant engagement in addressing challenges and practical solutions. Hands-on training involved demonstrations of AI-based tools such as adaptive learning platforms, virtual tutors, and automated evaluation applications. Evaluations indicated an increase in participants' understanding of AI usage and enthusiasm for integrating technology into teaching and learning activities. This program not only enriched participants' skills but also provided strategic solutions to enhance the effectiveness of technology-based education. This approach is expected to create a modern, adaptive, and sustainable learning ecosystem in the school.